Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.

Role of structural distortion in stabilizing electrosynthesized blue emitting phosphorene quantum dots - Valappil, Manila Ozhukil; Joshi, Krati; John, Lisa; Krishnamurthy, Sailaja; Jana, Bikash; Patra, Amitava; Pillai, Vijayamohanan K.; Alwarappan, Subbiah (Journal of Physical Chemistry Letters, 2019)
Luminescent phosphorene quantum dots (PQDs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Herein, we investigate the structural distortion of black phosphorus (BP) under an applied electric field to yield blue luminescent PQDs [average diameter 8 +/- 1.5 nm (N = 60)]. The electrosynthesized PQDs exhibit photoluminescence emission independent of excitation wavelength with 84% quantum efficiency. Structural distortion that occurred during the transformation of BP to PQDs is confirmed by results obtained during transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Further, using first-principles-based density functional theory, calculations on oxygenated and nonoxygenated PQDs augment the experimental observations that an optimum oxygen content maintains the structural integrity of PQDs, above which the structural robustness of PQDs is drastically diminished.